Effect of Polymer Structure and Incorporation of Nanoparticles on the Behavior of Syndiotactic Polypropylenes. Issue 22 (25th August 2013) - Bejarano, Julian; Benavente, Rosario; Pérez, Ernesto; Wilhelm, Manfred; Quijada, Raúl; Palza, Humberto
<x xml:space="preserve">Abstract</x> A syndiotactic polypropylene (sPP) homopolymer and its copolymer with 1.4 mol% of norbornene (NsPP) are synthesized using a metallocene catalyst and the effect on the main properties of the addition of 4 wt% of either silica nanoparticles or multiwalled carbon nanotubes (CNTs) is studied. Important changes are observed in the thermal behavior of the different samples, primarily related to a strong nucleating effect of the nanofillers, much larger in CNTs than in silica, and to cold crystallization processes in the copolymer. Moreover, a rather relevant effect of the nanoparticles and their type, and of the cyclic comonomer is observed on the mechanical behavior of the polymer in the solid state. A strong effect of the kind of nanoparticle is also observed in the melt rheological properties of the samples, where again CNTs render larger changes than silica nanoparticles. On the contrary, oxygen permeation of sPP is unchanged with the addition of nanoparticles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>